Reference values for Cobb angles when evaluating the spine in the sagittal plane: a systematic review with meta-analysis - Furlanetto,Tássia Silveira (2018)
The present systematic review of observational studies with meta-analysis aim to identify the reference values of the spinal curvatures in the sagittal plane, as evaluated using the Cobb angle in X-rays, in healthy individuals. Electronic searches were undertaken in MEDLINE, Scopus, ScienceDirect and LILACS. Studies that evaluated the spinal curvature of healthy children, adolescents, adults, and elderly using Cobb method and presented reference values for those curvatures were incluced. Thirty-one studies were eligible for inclusion. The reference values found (confidence interval 95%) were: for children, thoracic (28.7°-37.9°), lumbar L1-L5 (34.5o-44.8º), and lumbar L1-S1 (41.7o-54.1o); for adolescents: thoracic (31.5o-39.2o), lumbar L1-L5 (39.8o-45.6o), and lumbar L1-S1 (51.9o-59.1o); for adults: thoracic (33.7o-40.3o), lumbar L1-L5 (38.1o-45.6o), and lumbar L1-S1 (54.2o-61.7o); and for the elderly: thoracic (37.7º-50.4o), and lumbar L1- S1 (56.6º-65.9o). For the cervical region, it was impossible to establish consistent reference values. The present study supports that precise reference intervals were identified for the sagittal curvatures of the thoracic and lumbar spine in healthy children, adolescents, adults and elderly, as evaluated by means of the Cobb Method.